2003
DOI: 10.1080/0953710031000137046
|View full text |Cite
|
Sign up to set email alerts
|

Neonates born to pre-eclamptic mothers have a higher percentage of natural killer cells (CD3 - /CD56+16+) in umbilical cord blood than those without pre-eclampsia

Abstract: Objective: Maternal endothelial dysfunction and intravascular inflammation have been implicated in the mechanisms of disease responsible for the clinical syndrome of pre-eclampsia. Recently, the activation of the innate limb of the immune response (neutrophils and monocytes) in the fetal circulation has been reported in neonates born to mothers with pre-eclampsia. Natural killer (NK) cells are identified morphologically as a subpopulation of lymphocytes, but functionally as one component of the innate immune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Family D had 2 generations each containing a single affected individual. Patients A-II-2 and A-III-1 are the original YPS patients described by Dr. James White (15-18). Platelet EM findings of patient B-II-2 have been previously reported (14).…”
Section: Resultsmentioning
confidence: 99%
“…Family D had 2 generations each containing a single affected individual. Patients A-II-2 and A-III-1 are the original YPS patients described by Dr. James White (15-18). Platelet EM findings of patient B-II-2 have been previously reported (14).…”
Section: Resultsmentioning
confidence: 99%
“…Using the intracellular marker Foxp3 is therefore superior and more accurate. Interestingly, some studies have shown an association between preeclampsia and changed levels of T cell subpopulations in umbilical cord blood, showing an alteration in the immunological parameters of the newborn (27,28).…”
Section: Decreased Tregs In Preeclampsia 301mentioning
confidence: 99%
“…One has considerably lowered activity in comparison to NK cells in adults, while the other has properties similar to the observed in people with mature immunological system. Number of NK cells, both under the influence of infection and certain non-infectious risk factors, mainly hypoxia, undergo dynamic changes [13]. Neonates with infections, regardless to fetal age, had lower percentage of NK cells, it concerns both term and premature neonates.…”
Section: Discussionmentioning
confidence: 98%